PENERTIBAN PEDAGANG KAKI LIMA OLEH SATPOL PP DI PASAR PAGI ARENGKA KOTA PEKANBARU - Atun, Umi; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru is one of the city that became the target of the urban to create jobs in informal sector, which is the street vendors. The street vendors who selling on the road and troatoar and buyers on the road vehicle parked next pagi Arengka market resulted in the slow lane can not be by passed so that the front area of the pagi Arengka market become disorderly and disruptive comfort of road users and local residents. The problem in this research is how control of the street vendors by police unit of pamong praja in pagi Arengka market and the factors that influence the control of street vendors by police unit of pamong praja in the pagi Arengka market pekanbaru.research methods used in this research is qualitative research. Conduct an interviews snowball sampling technique, the key informants in this study. The informant who conducted the interview was from police unit of pamong praja pekanbaru.The results of this study indicate that the control vendors by police unit of pamong praja in the pagi Arengka market pekanbaru is not optimally. Factors that influence the control of street vendors by police unit of pamong praja in pagi Arengka market is because the police unit of pamong praja do not have a Standard Operating Procedure (SOP), a lack of human resources in terms of quantity and quality and the lack of community participation to run the rule.Keywords: Management, Control, Street vendors